Empowering Educators through Strategic IT Management: A Study on Enhancing Teacher's Technological Competence - Armiya, Armiya; Fatmawati, Nurul (Development: Studies in Educational Management and Leadership, 2023)
This study aims to propose a model for the implementation of strategic management to enhance IT teaching competencies among teachers at SMK Babusalam, Baktiya, North Aceh. Adopting a qualitative approach with five respondents, data was collected through observation, interviews, and documentation, followed by descriptive analysis. The findings reveal that strategic management was implemented through various teacher development training programs, including In-house Training, Subject Teacher Working Group (MGMP), and collaborative training with other schools. This approach not only reduced costs but also strengthened inter-institutional cooperation. The enhancement of competencies was assessed based on the ability to utilize networked learning software and create effective instructional media. The implementation process was influenced positively by supportive factors such as well-equipped Multimedia Laboratories and the availability of IT resources. However, personal factors posed as challenges. The results provide valuable insights into strategic management strategies for improving IT teaching competencies.